Maize Farmer Partnership Sustainability Study in the Post Arisa Project (Applied Research and Innovation System in Agriculture) in Kayangan District, North Lombok Regency - Ajeng Kartika Pratiwi; I Wayan Suadnya; I. G. L Parta Tanaya; I Ketut Budastra; Taslim Sjah (Jurnal Biologi Tropis, 2022)
The University of Mataram is coordinating the ARISA Corn (Applied Research and Innovation System in Agriculture) Intervention Project, which includes partners such as Bank NTB Syariah, PT. Syngenta, the Department of Agriculture, Retailer of Subsidized Fertilizers, and buyers of produce have exceeded their target of increasing 30% in revenue. The purpose of this study consisted of a general objective, namely to analyze the sustainability of the ARISA partnership project in the village of Gumantar, Kayangan District, North Lombok Regency and a specific purpose to analyze the sustainability of the partnership of corn farmers who carried out the ARISA project in the village of Kayangan District, North Lombok Regency. This study uses descriptive methods and data collection techniques with survey techniques. The sampling technique used was purposive sampling (deliberately) with the consideration that only 1 of these villages participated in the ARISA project at the beginning of the project. The technique of determining respondents using proportional sampling was determined by 15 respondents because only the corn farmers participated in the ARISA project from the beginning to the end of the project. The data analysis used is qualitative descriptive analysis. The results show that the sustainability of the partnership in the ARISA project is still ongoing even though the program has ended in 2018. The partnership between farmers and Unram does not continue in terms of the application of technology. The partnership with Bank NTB Syariah through the application of people's business credit applications and purchasing inputs according to recommendations with new suppliers is still ongoing. Field agricultural extension staff manage and coordinate fertilizer distribution with RDKK and merchants. The collaboration with yield buyers continues with new purchasers.